Naive freedom. Against the compatibilist perspectivism of Spinoza and Dennett - Jaime Nieto, Juan Pablo (2024)
The current work tries to make an exposition on the origins of negative conception ofignorance in the ancient, medieval and modern eras of the occidental philosophy. The purpose is to synthetize a general idea for each of these eras in the voice of some of their detractors, giving this way a first step for future apologies of the ignorance and the ways it benefits us intellectually, considering that the documentary research and the new ignorance’s studies opens a path for a methodology of historic comparison that allows a wider gaze about this topic.